2017
DOI: 10.1002/erv.2539
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and Cognitive Correlates of Recovery in Anorexia Nervosa

Abstract: Objective To identify clinical or cognitive measures either predictive of illness trajectory or altered with sustained weight-recovery in adult women with anorexia nervosa. Methods Participants were recruited from prior studies of women with anorexia nervosa (AN-C) and in weight-recovery following anorexia nervosa (AN-WR). Participants completed a neuropsychological battery at baseline and clinical assessments at both baseline and follow up. Groups based on clinical outcome (continued eating disorder, AN-CC;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 74 publications
1
25
0
Order By: Relevance
“…Recovered AN patients do not significantly differ from controls in important elements of social functioning, in terms of empathy, emotional recognition, or social conformity according to one study (Morris et al, 2013). Self-liking was found to not significantly differ between sustained weight-restored AN and acutely ill AN (Harper et al, 2017), whereas self-esteem was lower than healthy controls in both recovered AN (Brockmeyer et al, 2013) and BN patients (Daley et al, 2008).…”
Section: Quality Of Life and Positive Mental Healthmentioning
confidence: 77%
See 3 more Smart Citations
“…Recovered AN patients do not significantly differ from controls in important elements of social functioning, in terms of empathy, emotional recognition, or social conformity according to one study (Morris et al, 2013). Self-liking was found to not significantly differ between sustained weight-restored AN and acutely ill AN (Harper et al, 2017), whereas self-esteem was lower than healthy controls in both recovered AN (Brockmeyer et al, 2013) and BN patients (Daley et al, 2008).…”
Section: Quality Of Life and Positive Mental Healthmentioning
confidence: 77%
“…Alexithymia was found to be greater in recovered AN compared to controls in one study and not differ significantly between sustained weight-restored AN and acutely ill AN patients in another (Harper et al, 2017). Schizotypal features such as suspiciousness, intimacy and identity issues, interpersonal inhibition, and social avoidance (Holliday, Uher, Landau, Collier, & Treasure, 2006;McAdams & Krawczyk, 2011) were found to improve in AN but were elevated compared to controls and not differ significantly from acutely ill patients.…”
Section: Comorbid Psychiatric Symptoms and Psychopathologymentioning
confidence: 87%
See 2 more Smart Citations
“…Similarly, there are significant differences observed between people currently ill with AN and those recently recovered from AN on measures of cognitive flexibility, such as set-shifting tasks (Harper, Brodrick, Van Enkevort, & McAdams, 2017). Poor cognitive flexibility has been shown to relate to longer and more severe AN symptomatology (Westwood, Eisler, et al, 2016;Westwood, Stahl, et al, 2016), and 10 years after recovery from AN, healthy set-shifting is observed (Gillberg, Råstam, Wentz, & Gillberg, 2007).…”
mentioning
confidence: 99%